Speech dereverberation enhancement - Khalifa, Othman Omran; Hasmad, Safiyah; Abdul Malik, Noreha (2020)
Reverberation is the process of multi-path propagation of a sound from its source to a receiver. It is a blind problem where the source signal is un-known and non-stationary as well as the acoustic channel also unknown and time-varying. Therefore, the effect of reverberation on speech causes sound distant and spectrally distorted and can also reduce intelligibility. Derever-beration is therefore an important speech enhancement. However, different methods were proposed to reduce the noise with keeping the original signal as natural as possible. In this paper, a method was proposed using Wiener fil-ter approach to enhance the reverberated speech signals. The mechanism and the theories of the Wiener filter on how to enhance the speech is fully ex-plained. In addition, Discrete Fourier Transformation, linear spectrum nor-malization, correlation algorithms are explained in detail. The techniques of Wiener filter has been implemented and the desired results of enhanced speech have been obtained successfully.